PEMBELAJARAN KREA TIF•PRODUKTIF UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF BAGI MAHASISWA - Pratiwi Pujiastuti (Fakultas Ilmu Pendidikan UNY, 2009)
A creative-productive learning is one learning model emphasizing the students to be active or a student-centered learning. This learning model challenge the students in developing creativity to produce a product derived from their understanding on the concept studied. The learning climate is interesting, challenging, enjoyable and meaningful to the students. The creative-productive learning model includes: active students' involvement, both intellectual and emotional, through exploring the concept to be studied. the students construct the concept studied by themselves, and the students are responsible for completing the task. The students active in attending the learning process is the important requirement in developing the critical and creative thinking skill: suchskill needs to be trialed to the students through the creative-producttve learning model. Many concepts are taught using the creative-productive learning model; the lecturer is expected to try this learning model. Keywords: The creative-productive learning model, critical-creative thinking skill